A Receptor Guanylate Cyclase, Gyc76C, Mediates Humoral, and Cellular Responses in Distinct Ways in Drosophila Immunity - Iwashita, Shinzo; Suzuki, Hiroaki; Goto, Akira; Oyama, Tomohito; Kanoh, Hirotaka; Kuraishi, Takayuki; Fuse, Naoyuki; Yano, Tamaki; Oshima, Yoshiteru; Dow, Julian A. T.; Davies, Shireen-Anne; Kurata, Shoichiro (Frontiers in Immunology, 2020)
Innate immunity is an evolutionarily conserved host defense system against infections. The fruit fly Drosophila relies solely on innate immunity for infection defense, and the conservation of innate immunity makes Drosophila an ideal model for understanding the principles of innate immunity, which comprises both humoral and cellular responses. The mechanisms underlying the coordination of humoral and cellular responses, however, has remained unclear. Previously, we identified Gyc76C, a receptor-type guanylate cyclase that produces cyclic guanosine monophosphate (cGMP), as an immune receptor in Drosophila. Gyc76C mediates the induction of antimicrobial peptides for humoral responses by a novel cGMP pathway including a membrane-localized cGMP-dependent protein kinase, DG2, through downstream components of the Toll receptor such as dMyD88. Here we show that Gyc76C is also required for the proliferation of blood cells (hemocytes) for cellular responses to bacterial infections. In contrast to Gyc76C-dependent antimicrobial peptide induction, Gyc76C-dependent hemocyte proliferation is meditated by a small GTPase, Ras85D, and not by DG2 or dMyD88, indicating that Gyc76C mediates the cellular and humoral immune responses in distinct ways.